2021
DOI: 10.2147/jaa.s307165
|View full text |Cite
|
Sign up to set email alerts
|

MiR-21-5p in Macrophage-Derived Exosomes Targets Smad7 to Promote Epithelial Mesenchymal Transition of Airway Epithelial Cells

Abstract: Background: Asthma is usually associated with airway inflammation and airway remodeling. Epithelial mesenchymal transition (EMT) often occurs in airway remodeling. The purpose of this study is to identify the effect of miR-21-5p and Smad7 signaling pathway in macrophage-derived exosomes on EMT of airway epithelial cells. Methods: HE staining and Masson staining were used to verify the successful establishment of the asthma model. The levels of epithelial cell adhesion factor and stromal cell markers were detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“… Deng et al (2010) found that the abundant expression of tumor necrosis factor α (TNFα) and interleukin-6 (IL-6) by macrophages can create a favorable inflammatory environment for the occurrence of colonic adenocarcinomas. Moreover, macrophages play a considerable role in the acquisition of the epithelial– mesenchymal transition (EMT) hallmarks observed in gastric cancer tissues ( Guan et al, 2021 ), pancreatic duct epithelial cells ( Otto et al, 2021 ), and tracheal epithelial cells ( Li et al, 2021 ), and EMT signatures plays a vital role in tumor metastasis ( Lu and Kang, 2019 ). Macrophages are heterogeneous cell clusters with intricate functions and forms.…”
Section: Introductionmentioning
confidence: 99%
“… Deng et al (2010) found that the abundant expression of tumor necrosis factor α (TNFα) and interleukin-6 (IL-6) by macrophages can create a favorable inflammatory environment for the occurrence of colonic adenocarcinomas. Moreover, macrophages play a considerable role in the acquisition of the epithelial– mesenchymal transition (EMT) hallmarks observed in gastric cancer tissues ( Guan et al, 2021 ), pancreatic duct epithelial cells ( Otto et al, 2021 ), and tracheal epithelial cells ( Li et al, 2021 ), and EMT signatures plays a vital role in tumor metastasis ( Lu and Kang, 2019 ). Macrophages are heterogeneous cell clusters with intricate functions and forms.…”
Section: Introductionmentioning
confidence: 99%
“…As in silico analysis does not suggest a direct link between the two, we investigated possible pathways. miR‐21 regulates the TGF‐β signaling pathway by targeting mothers against decapentaplegic homolog 7 (SMAD7), ultimately leading to an increase in TGF‐β 35,36 . In mice, nerve Tgfb is increased after nerve injury 10 .…”
Section: Discussionmentioning
confidence: 99%
“…MiR-21 was also strongly stained in alveolar macrophages, known source of TGF-β. Alveolar macrophages were found to produce high levels of miR-21 containing liposomes, which induced EMT in tracheal epithelial cells through TGF-β1/Smad signaling pathway (26). Therefore, it is reasonable to hypothesize that alveolar macrophages play a central role in promoting fibroproliferative mechanisms by secreting exosomes containing fibrosis inducers such as cytokines and miRNAs.…”
Section: Discussionmentioning
confidence: 99%